2013
DOI: 10.1179/1351000212y.0000000038
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of alpha-tocopherol and ascorbic acid in combating ethanol-induced hepatic fibrosis

Abstract: Combined administration of fat soluble AT and water soluble AA was beneficial against ethanol-induced hepatotoxicity. This may be due to their different subcellular localizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…These results indicated that the levels of NF-kB were significantly reduced in rats administrated with basic curcumin and were confirmed by Simone et al, (2009) who demonstrated that curcumin has been shown to inhibit nuclear factor κB (NF-κB) activation at several steps in the NF-κB signaling pathways and thereby controls numerous NF-κB-regulated genes involved in various diseases. It was clear from the present study that a significant increase in liver NF-kB levels were induced by administration of ascorbic acid in agreement with the reports of Prathibha et al, (2013), presence of copper in comination with improved the liver NF-kB levels in disagreement with the reports of Persichini et al, (2006) who demonstrated that copper activates the transcription factor NF-kappaB n the liver and lung tissues of rats, and that this effect is mediated by oxidative stress. Caspase-3 is a downstream effector cysteine protease in the apoptotic pathway.…”
Section: Discussionsupporting
confidence: 80%
“…These results indicated that the levels of NF-kB were significantly reduced in rats administrated with basic curcumin and were confirmed by Simone et al, (2009) who demonstrated that curcumin has been shown to inhibit nuclear factor κB (NF-κB) activation at several steps in the NF-κB signaling pathways and thereby controls numerous NF-κB-regulated genes involved in various diseases. It was clear from the present study that a significant increase in liver NF-kB levels were induced by administration of ascorbic acid in agreement with the reports of Prathibha et al, (2013), presence of copper in comination with improved the liver NF-kB levels in disagreement with the reports of Persichini et al, (2006) who demonstrated that copper activates the transcription factor NF-kappaB n the liver and lung tissues of rats, and that this effect is mediated by oxidative stress. Caspase-3 is a downstream effector cysteine protease in the apoptotic pathway.…”
Section: Discussionsupporting
confidence: 80%
“…Several groups have shown that subjects with alcoholic liver disease have been shown to have significantly lower plasma vitamin E levels [9,37,38] and a higher degree of redox imbalance [7]. However, the results of long-term vitamin E supplementation have been controversial and inconsistent [5,14,39,40] although positive results have been reported in patients with non-alcoholic fatty liver [20,21].…”
Section: Discussionmentioning
confidence: 97%
“…The consequential change in redox imbalance caused by ROS generation has been observed in patients with alcoholic liver disease [7] but attempts to ameliorate these disturbances through the administration of antioxidants has met with mixed results [1,8,9]. In contrast to this, many animal model studies (principally with rodents) have shown that these antioxidants and vitamin E in particular do have mitigating effects on free radical damage of the liver related to alcohol abuse [10][11][12][13][14]. Much of the damage appears to be associated with peroxidation of lipid membranes as use of N,N-Diphenyl-P-Phenlylenediamine (DPPD) a lipid radical scavenger has been shown to prevent oxidation and liver cell death in α-tocopherol (a form of vitamin E) deficient rats and cultured hepatocytes [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have shown that subjects with alcoholic liver disease have been shown to have significantly lower plasma vitamin E levels [9,37,38] and a higher degree of redox imbalance [7]. However, the results of long-term vitamin E supplementation have been controversial and inconsistent [5,14,39,40] although positive results have been reported in patients with non-alcoholic fatty liver [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The consequential change in redox imbalance caused by ROS generation has been observed in patients with alcoholic liver disease [7] but attempts to ameliorate these disturbances through the administration of antioxidants has met with mixed results [1,8,9]. In contrast to this, many animal model studies (principally with rodents) have shown that these antioxidants and vitamin E in particular do have mitigating effects on free radical damage of the liver related to alcohol abuse [10][11][12][13][14]. Much of the damage appears to be associated with peroxidation of lipid membranes as use of N,N-Diphenyl-P-Phenlylenediamine (DPPD) a lipid radical scavenger has been shown to prevent oxidation and liver cell death in α-tocopherol (a form of vitamin E) deficient rats and cultured hepatocytes [3,15].…”
Section: Introductionmentioning
confidence: 99%